2019
DOI: 10.4103/ajts.ajts_83_18
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric enumeration of CD34+ hematopoietic stem cells: A comparison between single- versus dual-platform methodology using the International Society of Hematotherapy and Graft Engineering protocol

Abstract: BACKGROUND: Flow cytometric enumeration of CD34+ hematopoietic stem cells (HSC) is the reference point for undertaking apheresis and evaluation of adequacy for peripheral blood stem cell (PBSC) engraftment. AIMS: To determine whether single platform correlates with dual platform methods in CD34+ enumeration using ISHAGE protocol. METHODS: Retrospective analysis of CD34 Enumeration assays on both peripheral blood and PBSC product samples using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 8 publications
(10 reference statements)
0
10
0
Order By: Relevance
“…As single-platform assays have the potential to be more effective in reducing interlaboratory variation than dual-platform techniques in CD34 enumeration, determining MNC count through CD34 enumeration plot by flow cytometry shall provide instant value with ease of procedure. [ 3 6 ] As absolute MNC count in harvest was an easily accessible and alternative variable to assess the adequacy of hematopoietic stem cell collection, it gains importance in centers where CD34+ cell enumeration was outsourced. The study observed a significant difference between MNC doses estimated between these two methods ( P = 0.047) [ Table 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As single-platform assays have the potential to be more effective in reducing interlaboratory variation than dual-platform techniques in CD34 enumeration, determining MNC count through CD34 enumeration plot by flow cytometry shall provide instant value with ease of procedure. [ 3 6 ] As absolute MNC count in harvest was an easily accessible and alternative variable to assess the adequacy of hematopoietic stem cell collection, it gains importance in centers where CD34+ cell enumeration was outsourced. The study observed a significant difference between MNC doses estimated between these two methods ( P = 0.047) [ Table 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] Hematopoietic stem cells are identified by dim CD45 expression/low side scatter and CD34+ population using sequential Boolean gating strategy in flow cytometry. [ 2 3 ]…”
Section: Introductionmentioning
confidence: 99%
“…This cell surface markers are mostly glycoproteins referred to as clusters of differentiation (CD) markers which aid in differentiating cell subpopulations [2], Example CD44 + , CD38 -, CD38 -CD90 + (thy-1), CD117 + (c-kit), CD34 + and CD45 + CD49f + and lineage markers (CD14 -, CD8 -) This report describes the SOP for enumeration of HSCs in PB in other to evaluate the patient need for transplantation, which is dependent on donor and recipients matching, graft-versushost response or leukaemia effect [3]. Accurately, enumerating HSCs will assist in the subsequent plans for apheresis collection [4].…”
Section: Clinical Association and Potential Diagnosismentioning
confidence: 99%
“…Blood samples were taken from the tail vein on days 1, 10, 30 and 60. The proliferative activity of CD34 + stem cells was studied using a CD34 Countkit 24,25 kit for cytofluorimetry via a FACS Calibur flow cytofluorometer. The digital material was processed using the analysis of variance, Student's/ Bonferroni modification (Figure 1).…”
Section: Stimulating the Growth Of Cd34 + Pluripotent Hematopoietic Cmentioning
confidence: 99%